Estimation of the Critical Pressure Based on the Molecular Structure - Lai, Ngoc Anh; Le, Xuan Tuan; Ta, Van Chuong; Pham, Thai Son (Old Journal, 2017)
A study on the estimation of critical pressure of working fluids in thermodynamic cycles based on molecular structure was carried out. The calculation flow chart for the determination of the critical pressure based on Joback method was presented in this study. This paper also presented the calculation flow chart for the determination of the critical pressure based on our proposed modified Joback method. The calculated critical pressures of HFO-1234yf, HFO-1234ze(E), and HFO-1243zf showed that the proposed modified Joback method is more accurate than the conventional Joback method. Due to the lack of experimental data and the accuracy of the modified Joback method, the critical pressures of 9 Hydrofluoroolefins (HFOs) as R1225yc, R1225zc, R1234yc, R1234ye (E), R1234ze(Z), R1243ye, R1243yf, R1243zc, and R1243ze(E) have been determined by the modified Joback method.